Exploring City Branding Potential of Malang as Differentiation Method in Promotion - Nur Kholis; Bambang Dwi Prasetyo; Mardiono Mardiono (Wacana Journal of Social and Humanity Studies, 2017)
Marketing communication and promotion is the most essential thing in brand development. As a brand, Malang should apply it in order to compete with other cities, more particularly in terms of economic, social, cultural and tourism sector. Malang has potentials that will attract both visitors and investors. City branding should become one of the governmentâ€™s focus to build its brand. It is the manifestation of city marketing in which objective is to highlight its strength. Based on the researchersâ€™ observation, Malang has yet had attracting city branding composition. The objectives of the research were to collect and analyze all potential assets Malang had to strengthen its identity as a tool to formÂ  city branding. It provided a suggestion to Malang City government in a form of tagline positioning and promotion strategy. The researchers developed a city branding concept for the city and came up with a tagline associated with Malang. The study used qualitative approach and in-depth interview. Based on the analysis, the researcher suggests a tagline â€œYour Home Sweet Homeâ€ as a part of Malang city branding. In addition, the researchers also proposed minor and major proposition. The minor proposition was education sector was the biggest asset Malang had. Therefore, there should be integration between the sector and other activities more particularly ones related to the culture, history and local wisdom of Malang. Furthermore, the major proposition was every city should explore its differentiation that will attract visitors and investors.